Replanteo e instalación de alcantarillas en una carretera - Farías Meza, Juan A. (2009)
In this Seminar Graduation Thesis is the Settle and Instalation of Pipes in a Highway. The purpose is to show the Field and Oficce tasks of the Civil Ingeneers in the execution of the Drainage Works to ensure in the professional a good development, the knowledge and use of standars and constructive techniques to obtain optimal finish and fulfil the design of the Drainage System. To show this we use data of a Highway. The development of this works is based on knowledge acquired in the Highway Seminar Graduation, in addition of processes described in many Guide Texts and Handbooks which outline the building techniques used in earthmovement, Pipe installation, Fillings, architectural works; in addition of helpful criteria to interpret the Technical Documentation, Selection of Heavy Duty Machine and Equipment; finally, the experience of Local Building Professional.